The Microbiota-Gut-Brain Axis in Health and Disease and Its Implications for Translational Research - Schächtle, Melanie Anna; Rosshart, Stephan Patrick (Frontiers in Cellular Neuroscience, 2021)
Over the past decades, microbiome research has evolved rapidly and became a hot topic in basic, preclinical and clinical research, for the pharmaceutical industry and for the general public. With the help of new high-throughput sequencing technologies tremendous progress has been made in the characterization of host-microbiota interactions identifying the microbiome as a major factor shaping mammalian physiology. This development also led to the discovery of the gut-brain axis as the crucial connection between gut microbiota and the nervous system. Consequently, a rapidly growing body of evidence emerged suggesting that the commensal gut microbiota plays a vital role in brain physiology. Moreover, it became evident that the communication along this microbiota-gut-brain axis is bidirectional and primarily mediated by biologically active microbial molecules and metabolites. Further, intestinal dysbiosis leading to changes in the bidirectional relationship between gut microbiota and the nervous system was linked to the pathogenesis of several psychiatric and neurological disorders. Here, we discuss the impact of the gut microbiota on the brain in health and disease, specifically as regards to neuronal homeostasis, development and normal aging as well as their role in neurological diseases of the highest socioeconomic burden such as Alzheimer´s disease and stroke. Subsequently, we utilize Alzheimer’s disease and stroke to examine the translational research value of current mouse models in the spotlight of microbiome research. Finally, we propose future strategies on how we could conduct translational microbiome research in the field of neuroscience that may lead to the identification of novel treatments for human diseases.